Study and modelling of a heterogeneous debris slide (Journal of Nepal Geological Society, 2000)
The paper describes a new approach to the study of heterogeneous debris slides. For this purpose, an investigation was carried out in the field as well as the laboratory. The two-dimensional computation techniques of Distinct Element Method were applied for the prediction of the displacements in the landslide. The predictions accord well with the results of inclinometer measurements in the landslide. This technique can he applied with some modifications to many soils that can be treated as heterogeneous debris (silty-clayey matrix with big boulders), such as those found along the Alpine arc. The study also demonstrates that it is possible to adapt the mathematical models implemented in the up-to-date calculation programs for particular needs, even if this is to the validity limits of the theory.